On the existence and uniqueness of the solution of a differential equation with interaction governed by generalized function in abstract wiener space - Brayman, V.B. (Інститут математики НАН України, 2005)
We consider some the following differential equation with interaction governed by a generalized function/ The conditions that guarantee the existence and uniqueness of a solution when
mapping a belongs to some Sobolev space are obtained.